The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1080/713608373
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Human Relevance Analysis of Information on Carcinogenic Modes of Action

Abstract: The human relevance framework (HRF) outlines a four-part process, beginning with data on the mode of action (MOA) in laboratory animals, for evaluating the human relevance of animal tumors. Drawing on U.S. EPA and IPCS proposals for animal MOA analysis, the HRF expands those analyses to include a systematic evaluation of comparability, or lack of comparability, between the postulated animal MOA and related information from human data sources. The HRF evolved through a series of case studies representing severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
190
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 405 publications
(194 citation statements)
references
References 151 publications
2
190
0
2
Order By: Relevance
“…The key events in α 2u -globulin nephropathy associated tumorigenesis and associated histopathological features have been described in great detail (Swenberg and LehmanMcKeeman, 1999;Meek et al, 2003). Yet it has been our experience in reviewing the results of the studies shown in Table 3 that the syndrome actually presents in a wide variety of ways.…”
Section: Discussionmentioning
confidence: 99%
“…The key events in α 2u -globulin nephropathy associated tumorigenesis and associated histopathological features have been described in great detail (Swenberg and LehmanMcKeeman, 1999;Meek et al, 2003). Yet it has been our experience in reviewing the results of the studies shown in Table 3 that the syndrome actually presents in a wide variety of ways.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been replicated in numerous comparable studies in Sprague Dawley rats (Barter and Klaassen 1994;Capen 1997;Hood et al 2003, Hood, Hashimi et al 1999Hood, Liu et al 1999;McClain et al 1989). Development of thyroid follicular hypertrophy, hyperplasia, and progression to neoplasia occured with chronic PB administration in rats (Capen 1997;McClain et al 1989;Meek et al 2003); however, similar patterns of thyroid hormone changes without thyroid tumorigenesis were seen in rats given other microsomal enzyme inducing compounds including 3-methylcholanthrene and pregnenolone-16-a-carbonitrile (Barter and Klaassen 1994;De Sandro et al 1992;Saito et al 1991).…”
Section: Effects Of Enzyme Induction On Endogenous Thyroid Hormones Imentioning
confidence: 99%
“…arises� Although it is often not explicit, the basic rationale for these schemes is based on the "universality" idea discussed at the outset of this paper-that observations in one setting suggest that similar results would be obtained in other settings, including the setting of the human population being protected� MoA does come in, but usually as a secondary factor and not in a particularly formal way� That is, existence of multiple positive studies is taken as evidence that effect is not specific to one species/system/study and may therefore be general� The justifying arguments for this assertion usually flow from policy, precedent, analogy with other cases, etc�, rather than from case-specific inferences� In WoE, judgment is necessary, but what the rationale and reasoning for conclusions may be is rarely explicit� This leads to disputation of the judgments based largely on ad hominem considerations-who is judging (and whether they are "unbiased") rather than on the soundness of their judgments per se� Our approach is aimed at making the connection between judgments and case-specific evidence more explicit� In this way, the discussion can focus on the scientific interpretation of specific observations and the degree to which that interpretation is supported by those observations, rather than on who is making the interpretation� It should foster a more scientific and objective evaluation of WoE� To the degree that the issues come down to evaluation of MoA, the soundness of the MoA conclusions for the animal studies and the question of whether humans have the same MoA elements, the HBWoE method is complementary to the Human Relevance/MoA framework (Boobis et al�, 2006;Cohen et al�, 2003;Meek et al�, 2003;Sonich-Mullin et al�, 2001)� Our approach makes more explicit how one should evaluate the MoA information, and it shows the value of looking beyond just the single-animal model in which the response is seen to consider what happens (and what does not happen) in other nontarget species and tissues� It calls attention to the role of inconsistent information, not just to the plausibility of the proposed MoA elements in setting where they produced the endpoint of interest� It emphasizes the role of wider scientific understanding in judging what reasonable inferences are, and it points out the pitfalls of post hoc reasoning about the potential role of MoA elements (remembering the example of direct air contact explaining the location of tumors)� HBWoE comes down to evaluation of alternative "accounts� " An account (which we put forth in this context as a technical term) is a proposed set of explanations for the set of observed phenomena across the body of relevant observations� The essence of the accounts is that they constitute being explicit about Bradford Hill's "ways of explaining the set of facts before us� " They are not conclusions or findings, but rather provisional proposals for the reasons behind the set of observations we have at hand, set out in a way that makes clear where assumptions, interpretations, and tentative inferences have been drawn� It is by comparing alternative accounts-alternative hypotheses about what causal effects actually exist-and assessing: their comparative success at explaining phenomena; their comparative need for assumptions to fill in gaps (and the comparative reasonableness of those assumptions); and their comparative invocation of ad hoc suppositions that are necessary to accommodate what might otherwise be inexplicable results, that we can judge how compelling each alternative should be deemed, and hence with what degree of confidence we can judge the hypothesized causal processes (and their consequences for human risk estimation) to be supported by the factual r...…”
Section: Discussionmentioning
confidence: 99%